2006
DOI: 10.1021/jf0616311
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Red Wine Marinades on the Formation of Heterocyclic Amines in Fried Chicken Breast

Abstract: Genotoxic heterocyclic amines (HAs) are formed via the Maillard reaction and free radical reaction mechanisms when meat or fish is cooked at usual cooking conditions. In this paper, the effect of the addition of red wine was tested to study if it interferes in HA formation. Fried chicken breast was the food item chosen, and three different red wines, characterized in terms of grape varieties, free amino acids, antioxidant properties, and metallic composition, were used to marinate meat prior to the heating pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 62 publications
6
54
2
2
Order By: Relevance
“…For instance, one of the most effective methods reported for the inhibition of the formation of PhIP has been marinating the meat with red wine previous to the cooking process involving heat, effect that was markedly different to control marinades containing water and ethanol (Busquets et al, 2006). An example of the reduction of PhIP in fried chicken with marinating time is shown in Fig.…”
Section: Parameters Affecting the Yield Of Hcasmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, one of the most effective methods reported for the inhibition of the formation of PhIP has been marinating the meat with red wine previous to the cooking process involving heat, effect that was markedly different to control marinades containing water and ethanol (Busquets et al, 2006). An example of the reduction of PhIP in fried chicken with marinating time is shown in Fig.…”
Section: Parameters Affecting the Yield Of Hcasmentioning
confidence: 99%
“…8 (Ahn et al 2005;Bermudo et al, 2005 ;Borgen et al, 2004;Busquets et al, 2004Busquets et al, , 2006Busquets et al, , 2008Casal et al, 2004;Cheng et al, 2007;Gerbl et al, 2004;Khan et al, 2008;Lan et al, 2004;Melo et al, 2008;Ni et al, 2008;Oz et al, 2007;Persson et al, 2004;Ristic et al 2004;Salmon et al, 2006;Toribio et al, 2007;Tsen et al, 2006;Warzecha et al, 2004;Wong et al, 2005). The average concentrations of several HCAs in meats cooked using different methods shows that chicken presents the highest concentration of HCAs, and in particular of the amines called DMIP and PhIP, which are structurally related, and the comutagens and neurotoxic amines harman and norharman, which were also found at relative high concentrations in venison.…”
Section: Levels Of Hcas In Foodmentioning
confidence: 99%
“…Several studies have shown that natural antioxidants in the form of spices, berries, wine or beer can reduce the formation of HCAs in beef [7] [8] [9], pork [10] [11] and chicken [12] [13]. As previous research has demonstrated, pork chops, in particular, are often marinated before barbecuing [14], and there exists the potential to produce marinades using antioxidant herbs and berries, thus reducing the risk of formation of HCAs during barbecuing.…”
Section: Introductionmentioning
confidence: 99%
“…However, in gastronomy, these taste-givers are mainly added to commercial marinades that also include other ingredients, and the impact of this more complex matrix has not been investigated. Furthermore, numerous investigations have focused on the ability of the active compound to reduce HCAs and have overlooked the sensory quality of the marinated meat [13] [15] [16]. However, it seems important to combine the chemical analysis of the effect of the compounds with a sensory and consumer study to evaluate the gastronomic value.…”
Section: Introductionmentioning
confidence: 99%
“…As pesquisas que vêm sendo feitas estão relacionadas ao uso de marinadas de vinho para temperar carnes e, assim, aproveitar o poder antioxidante dessa bebida. Marinar com vinho tinto é uma prática culinária muito utilizada em vários países, e serve para minimizar a formação de Aminas Heterocíclicas (AH), potencialmente carcinogênicas, em frangos fritos 12 . Melo et al 13 também observaram a redução na formação de AHs em bifes fritos, marinados previamente por até seis horas no vinho tinto.…”
unclassified